MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI DAN HASIL BELAJAR SISWA MELALUI MODEL PROJECT BASED LEARNING DI KELAS VIII MTS BAITUL MAKMUR, KOTA BENGKULU - Gyzka Veliesa; Saleh Haji; Hari Sumardi; Agung Setia Budi (MES: Journal of Mathematics Education and Science, 2023)
This study aims to improve students' high-order thinking skills through Project Based Learning in Class VIII at Mts Baitul Makmur, Rejang Lebong, Bengkulu. There were two cycles in this research. Each cycle applies a project-based learning model and consists of four stages, namely planning, implementing, observing, and reflecting.  The research subjects were 26 students of class VIII B at MTs Baitul Makmur Rejang Lebong. Data were collected through observation, field notes, documentation, and tests. The results showed that the implementation of project-based learning could improve students' high-level thinking skills. This is indicated by an increase in the percentage of higher-order thinking skills from pre-cycle (cycle 1 pre-test) of 48% (poor) to 73% (enough) in cycle 1. Then in cycle 2, it increased to 82% (good). Furthermore, there was an increase in student learning outcomes through the Project Based Learning model in Class VIII, Mts Baitul Makmur Rejang Lebong. In the pre-cycle, the average score of students' mathematics tests was 53.54, with classical completeness of 4%. In cycle 1, the average score increased to 76.62, with a classical pass of 73.08%. It increased in cycle 2, the average score being 80.12 with a classical pass of 85%.